EMPOWERING OLDER ADULTS IN HEALTH CARE DECISION MAKING. (11th November 2018) - Glicksman, A; Ring, L; Abbott, K M
Abstract: The often stated goal of empowering older adults to make their own decisions can be very difficult to implement in health care settings. The health of the older adult, including cognitive status, as well as limits placed on choices by diagnosis, available treatments and other factor such as cost often leave few choices in the hands of the patient. Each of the four papers on this panel presents findings from an intervention designed to maximize the opportunities for decision making on the part of the older adult. Stoop will describe comprehensive care programs in Europe that, amongst others, aim to improve involvement of older people and their informal caregivers in decision making and planning their care process. Scott's paper is on a program that empowers seniors by facilitating their healthcare needs with clear direction, consideration for the wishes and needs of the senior and family/caregiver, and provision of resources through the use of a brief cognitive screen. Hawkley and Huisingh-Scheetz will discuss their use of technology to enhance the decision making opportunities for older adults. Eisenstein will look at research as a way of engaging and empowering older residents in a long term care setting. Abbott will respond to the papers and discuss empowerment as a goal and the challenges to that goal in health care settings. The great diversity among the topics will provide a very comprehensive look at approaches designed to provide older adults and their caregivers with real choices in what can be very difficult circumstances.